Assessing decarbonisation pathways in Qinghai Province, China: an analysis based on the extended STIRPAT model and data visualisation - Li, Shun; Hua, Jie; Chi, Xin (Frontiers in Environmental Science, 2025)
IntroductionAs the world’s largest carbon emitter, China’s decarbonization efforts are critical to global climate governance. Existing studies have mainly focused on carbon emissions at the national level in China, with less attention paid to the provincial level, especially in analyzing less developed regions in northwest China (e.g., Qinghai Province). This study explores specific carbon reduction pathways for less developed provinces, represented by Qinghai Province, by analyzing in depth the potential carbon emission risks in the province.MethodsUsing data from Qinghai Province’s 14th Five-Year Plan and Vision 2035 documents, we developed three carbon reduction scenarios (baseline, moderate, and stringent). We used the extended STIRPAT (Stochastic Impacts of Population, Affluence, and Technology Regression) model and ridge regression to analyze the impacts of five key drivers: population size, primary electricity utilization, GDP per capita, primary industry output, and agricultural fertilizer use. Scenario projections are complemented by advanced visualization techniques to improve policy relevance.ResultsOur analysis reveals three important findings: (1) an environmental Kuznets curve pattern emerges between GDP per capita and carbon emissions; (2) population growth is recognized as a major driver of carbon emissions, with each 1% increase in population leading to a 3.184% rise in carbon emissions; and (3) the strategic development of primary electricity shows a huge potential for emission reduction. With stringent environmental protection measures, Qinghai can cap its carbon emissions by 2030, in line with national climate goals.DiscussionThese findings challenge conventional assumptions about underdeveloped regions’ climate roles, demonstrating that targeted provincial strategies can significantly contribute to national decarbonization goals. The inverted U-curve relationship suggests economic development and emission reduction can be synergistic post-threshold GDP levels. We recommend prioritized investments in renewable energy infrastructure and population-optimized urbanization policies. This provincial-level modeling approach provides a replicable framework for other developing regions balancing economic growth with climate commitments.